2023
DOI: 10.1080/03019233.2023.2200596
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of strength of blast furnace flue dust – iron oxide – fly ash composite briquette using ANOVA-based mathematical model

Abstract: Utilisation of by-products of an integrated steel plant improves productivity with diverse mix of raw materials used for iron making. The strength of a briquette made with Blast furnace flue dust and iron oxide with fly ash as a binder depends upon the briquetting pressure, particle size of fly ash, fly ash quantity, and curing temperature. In this study, the effect of process variables on the strength was investigated with ANOVA. The correlation between the process parameters and the strength was examined exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It is clear that a suitable eco-friendly use of BWFD has not been explored in the existing literature. Despite that, there is a promising avenue to consider this waste as a photocatalyst, primarily due to its predominant composition of hematite (α-Fe 2 O 3 ), a known low optical bandgap (2.3 eV) iron oxide [7,8]. α-Fe 2 O 3 is a naturally abundant and cost-effective material, as iron is one of the most abundant elements on earth [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that a suitable eco-friendly use of BWFD has not been explored in the existing literature. Despite that, there is a promising avenue to consider this waste as a photocatalyst, primarily due to its predominant composition of hematite (α-Fe 2 O 3 ), a known low optical bandgap (2.3 eV) iron oxide [7,8]. α-Fe 2 O 3 is a naturally abundant and cost-effective material, as iron is one of the most abundant elements on earth [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have directed their focus toward repurposing BFDW for some viable applications, e.g., civil construction [28,29], adsorption processes [3,30], briquette production [7,31], and wastewater treatment [5,32]. Recently, Guo et al [33] employed BFDW in producing Fe-C composite electrodes and demonstrated an impressive 95.8% indigo dye removal.…”
Section: Introductionmentioning
confidence: 99%